Everlasting hell… Towns in the period of three wars including WW I (1914–1920) – research provided on the example of Ułaszkowce and Jagielnica in eastern Galicia - Dolinovskyi, Volodymyr (City and War, 2021)
This article presents the view of war devastation in two towns in the eastern part of Galicia Jagielnica and Ułaszkowce. As both these towns were located on the border, they appeared to be the epicenter of battles and war events which had lasted for 6 years during three wars WWI, Polish-Ukrainian and Polish-Bolshevik. The consequences of the wars were huge material damages to urban infrastructure such as residential, economic and technical. The houses, farm and industrial buildings, roads, bridges, etc. were ruined. The war stopped the development of rational agriculture. Farmlands, crops and harvests, agricultural farm buildings with livestock and real estates were destroyed. Cattle breeding suffered greatly during the war. Forests were also exposed to losses caused by battles. The result of the war activities on the frontier areas were requisitions for the army and crimes committed both by soldiers and the local people, e.g. theft of food, grain, tools, and robbing houses and real estates. An important issue was the investment made for the reconstruction of areas affected by military actions.